ETR 300 Green Globe Sdn. Bhd. / Muhammad Saieef Hurairah Mohd. Yusof...[et al.] - Mohd. Yusof, Muahmmad Saieef Hurairah; Mohd. Saman, Abdul Hadi; Kamsar, Mohd. Fairuz; Mohamad Dar @ Uchu, Lokman; Borhan, Nur’ Atiqah (2008)
Green Globe Sdn. Bhd is a company that plant and supply dragon fruit. Green Globe Sdn. Bhd. using innovation tevhnology of machinery towards systematic process of production in effective. This business operates in Ting. 2, No. 13, Jalan Syed Hussain, 02600 Arau. Perlis.